2018
DOI: 10.1113/jp275758
|View full text |Cite
|
Sign up to set email alerts
|

Maternal exercise in rats upregulates the placental insulin‐like growth factor system with diet‐ and sex‐specific responses: minimal effects in mothers born growth restricted

Abstract: The insulin-like growth factor (IGF) system regulates fetoplacental growth and plays a role in disease programming. Dysregulation of the IGF system is implicated in several pregnancy perturbations associated with altered fetal growth, including intrauterine growth restriction and maternal obesity. Limited human studies have demonstrated that maternal exercise enhances fetoplacental growth and decreases cord IGF ligands, which may restore the placental IGF system in complicated pregnancies. This study investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(66 citation statements)
references
References 61 publications
2
64
0
Order By: Relevance
“…20 During pregnancy, rats exercised in progressively shorter duration and speed (17 m/min for 50 minutes in week 1, 13 m/min for 30 minutes in week 2, and 11 m/min for 20 minutes in week 3). Rats were exercised on a motorized treadmill (Columbus Instruments, Columbus, OH, USA) 5 days a week followed by 2 days of rest.…”
Section: Exercise Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…20 During pregnancy, rats exercised in progressively shorter duration and speed (17 m/min for 50 minutes in week 1, 13 m/min for 30 minutes in week 2, and 11 m/min for 20 minutes in week 3). Rats were exercised on a motorized treadmill (Columbus Instruments, Columbus, OH, USA) 5 days a week followed by 2 days of rest.…”
Section: Exercise Trainingmentioning
confidence: 99%
“…20 Maternal blood was collected via cardiac puncture and the pancreas, gastrocnemius, and dorsal fat were excised, weighed, snap frozen, and stored at -80°C. F2 fetuses were weighed and sexed using Sry qPCR on fetal tails as previously described.…”
Section: Postmortem Tissue Collectionmentioning
confidence: 99%
“…At 20 weeks of age, F1 females were mated with normal males (Mangwiro et al . ). For an overview of animal allocations with sample sizes, see Fig.…”
Section: Methodsmentioning
confidence: 97%
“…We recently demonstrated that the insulin‐like growth factor (IGF) system is dysregulated in placentae from F2 offspring of mothers born growth restricted (Mangwiro et al . ). A key finding of this study was that maternal exercise initiated before and continued throughout pregnancy (termed ‘ Exercise ’), but not exercise initiated in the final two‐thirds of pregnancy (termed ‘ PregEx ’), increased fetal weight (Mangwiro et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation